(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Inthis paper an attempt has been made to elicit opinions of the students as theusers of college library. A questionnaire method is used to identify theimpression of students towards the adequacy of library resources and servicesutilized by the students. Finally it highlights the major findings of the studyand offers some important suggestions for the overall improvement of thelibrary.